D-4F, an ApoA-I mimetic peptide ameliorating TRPA1-mediated nocifensive behaviour in a model of neurogenic inflammation. (January 2020) - Oehler, Beatrice; Kloka, Jan; Mohammadi, Milad; Ben-Kraiem, Adel; Rittner, Heike L
Background: High doses of capsaicin are recommended for the treatment of neuropathic pain. However, low doses evoke mechanical hypersensitivity. Activation of the capsaicin chemosensor transient receptor potential vanilloid 1 (TRPV1) induces neurogenic inflammation. In addition to the release of pro-inflammatory mediators, reactive oxygen species are produced. These highly reactive molecules generate oxidised phospholipids and 4-hydroxynonenal (4-HNE) which then directly activate TRP ankyrin 1 (TRPA1). The apolipoprotein A-I mimetic peptide D-4F neutralises oxidised phospholipids. Here, we asked whether D-4F ameliorates neurogenic hypersensitivity in rodents by targeting reactive oxygen species and 4-HNE in the capsaicin-evoked pain model. Results: Co-application of D-4F ameliorated capsaicin-induced mechanical hypersensitivity and allodynia as well as persistent heat hypersensitivity measured by Randell–Selitto, von Frey and Hargreaves test, respectively. In addition, mechanical hypersensitivity was blocked after co-injection of D-4F with the reactive oxygen species analogue H2 O2 or 4-HNE. In vitro studies on dorsal root ganglion neurons and stably transfected cell lines revealed a TRPA1-dependent inhibition of the calcium influx when agonists were pre-incubated with D-4F. The capsaicin-induced calcium influx in TRPV1-expressing cell lines and dorsal root ganglion neurons sustained in the presence of D-4F. Conclusions: D-4F is a promising compound to ameliorate TRPA1-dependent hypersensitivity during neurogenic inflammation.